International Brand Chanel's Opposition to the Dacosta + DC Painting Brand - MZ, Henky Solihin (Indonesian Journal of Law and Economics Review, 2026)
General Background: Trademark protection under Law Number 20 of 2016 concerning Trademarks and Geographical Indications constitutes a central pillar of intellectual property law in Indonesia, ensuring legal certainty, fair competition, and consumer protection within the international registration framework, including the Madrid Protocol. Specific Background: This study examines the opposition filed by CHANEL SARL against the registration of the DACOSTA + DC Painting trademark before the Directorate General of Intellectual Property (DGIP), based on alleged substantial similarity and claims related to well-known mark protection. Knowledge Gap: Although opposition mechanisms are formally available to international trademark owners, limited doctrinal analysis addresses how Indonesian authorities assess formal and substantive requirements in determining similarity and bad faith. Aims: This research aims to analyze the legal basis of the opposition, the rebuttal submitted by the DACOSTA applicant, and the juridical considerations underlying the DGIP decision to accept the application. Results: The findings demonstrate that the objection did not satisfy the formal and material requirements stipulated under Article 21 of Law Number 20 of 2016, as no dominant similarity or evidence of bad faith was proven; consequently, the DGIP lawfully registered DACOSTA + DC Painting in Class 18. Novelty: This article provides a focused normative legal examination of an international trademark opposition resolved in favor of a domestic applicant within Indonesia’s constitutive registration system. Implications: The decision confirms that opposition by a global brand does not automatically preclude national registration absent substantiated similarity and reputational proof, reinforcing legal certainty in Indonesian trademark law. Highlights: The objection failed to establish dominant resemblance under Article 21 of Law Number 20 of 2016. No proof of bad faith or reputational appropriation was demonstrated in the proceedings. The authority confirmed lawful acceptance of the Class 18 application under the constitutive registration regime. Keywords: Chanel, Dacosta, Objection, Intellectual Property, Brand